Type 1 diabetes in Brazil: a narrative overview of the Brazilian Type 1 Diabetes Study Group - Marilia Brito Gomes; Carlos Antonio Negrato; On Behalf of the Brazilian Diabetes Study Group (Diabetology & Metabolic Syndrome)
Abstract Background To evaluate the real-world care of Brazilian individuals with type 1 diabetes (T1D). Methods The Brazilian Type 1 Diabetes Study Group (BrazDiab1SG), was conducted in two waves, in all Brazilian geographical regions. The first enrolled 3,591 individuals with data obtained from medical records. The second evaluated 1,760 individuals with laboratory and genetic data performed at State University of Rio de Janeiro. Results In the first and second waves, the average HbA1c was 9.3% and 9.0%, HbA1c above 10%, 32.2% and 26.3%, and individuals with HbA1c < 7.0%, 13.2% and 13.5%, respectively. Intermediate/long plus short acting insulins was the commonest used treatment modality. Less than 30% of the individuals achieved good glycemic control. Individuals in pumps and insulin analogs had lower mean HbA1c. Diabetic retinopathy, chronic kidney disease, cardiac autonomic neuropathy, peripheral neuropathy and macrovascular diseases were found in 35.7%; 25.2%; 23.4%; 14.8% and 2,1%, respectively. The 10-year Steno type 1 risk engine (S1TRE) showing moderate and high risk was noted in 18.0% and 11.3% of individuals. Diabetic retinopathy was associated with all diabetes-related chronic complications. Severe hypoglycemia was reported by 19%, periodontal disease by 4. % and autoimmune diseases by 19.5% of individuals. European genomic ancestry prevailed in the whole sample even in those Black self-reported. HLA-DRB1*03:01 ~ DQA1*05:01 ~ DQB1*02:01 was the most frequent risk haplotype with the highest frequency in individuals who self-reported as White and the haplotype HLA-DRB1*09:01 ~ DQA1*03:01 g ~ DQB1*02:02 had the highest frequency among those self-reported as Black. European genomic ancestry was associated with the risk alleles: DRB1*03:01; DRB1*04:01; DRB1*04:02; DQA1*05:01 DQB1*02:01; DQB1*03:02 and African genomic ancestry with the protective alleles: DRB1*03:02; DRB1*11:01; and DRB1*15:03. Amerindian (43.6%, haplogroup C) and African (38.2%, haplogroup L3) were the most frequent matrilineal ancestries (MtDNA). European patrilineal ancestry was predominant, in approximately 85%, followed by African ancestry in approximately 9%. European haplogroups R1b and E1b were the most prevalent. Conclusions In both waves, Brazilian individuals with T1D presented poor glycemic control and high rates of diabetes-related acute and chronic complications. Our data has been used to improve T1D management driving public health policies in Brazil.